Private partnership in advancing social inclusion-based library transformation in Tabalong, South Kalimantan - Moh Ilham A Hamudy; M Saidi Rifky; Mukhlisha Hayuningtyas (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. Pustaka Bisa is a collaborative initiative between the Library Service and PT Adaro Indonesia, implemented as part of its Corporate Social Responsibility (CSR) scheme. However, based on field observations, the program’s impact on increasing residents’ economic capacity and literacy culture has remained limited. Research Methods. Using a qualitative descriptive method based on field research, data were collected through interviews with librarians, village managers, the Library Service, and PT Adaro Indonesia. Data Analysis. Interview and field data were analyzed to identify the implementation, challenges, and impacts of the social inclusion literacy program in Tabalong Regency. Results. The results of the analysis revealed that the program’s success still largely depended on one librarian with strong initiative. In addition, it is necessary to focus more on the role of other librarians. Focusing on the program’s sustainability, the results also showed that the lack of integration between library materials and training, weak post-training assistance, and limited synergy between agencies. Conclusion. This study concludes that it is essential to enhance librarian capacity, integrate literacy programs with local economic development, and establish collaborative policies among local governments, the private sector, and the central government.